Academic Administration Strategies for Enhancing Students’ Innovation Capability in Schools under the Primary Educational Service Area Office Surat Thani Area 2 - Jantaramas, Somrudee; Boonjit, Yanisa; Charoenwongrayap, Anu (Journal of Graduate Research, 2026)
The objectives of this research were to: 1) study the priority needs for academic administration that enhances students’ innovation capability; 2) develop academic administration strategies to enhance students’ innovation capability; and 3) evaluate the academic administration strategies developed to enhance students’ innovation capability. The research was conducted in three steps. Phase 1 involved studying the priority needs for academic administration that enhances students’ innovation capability. The sample consisted of 124 school principals selected through proportional stratified random sampling. The research instrument was a questionnaire. Phase 2 involved the development and validation of academic administration strategies to enhance students’ innovation capability. Data obtained from Phase 1 was used to analyze the internal and external environments through SWOT analysis and to construct a TOWS Matrix for strategy formulation. The proposed strategies were then verified through in-depth interviews with 10 experts. Phase 3 involved evaluating the developed strategies. The sample consisted of 40 school administrators selected through purposive sampling. The research instrument was an evaluation form. Data were analyzed using percentage, mean, and standard deviation. The results revealed that: 1) regarding the priority needs for academic administration that enhances students’ innovation capability, the top three development priorities were learning process development (PNImodified = 0.46), followed by measurement and evaluation (PNImodified = 0.45) and curriculum development (PNImodified = 0.44), respectively; 2) the academic administration strategies developed to enhance students’ innovation capability consisted of three main strategies, six sub-strategies, and twenty-four measures; and 3) the academic administration strategies developed to enhance students’ innovation capability were rated at the highest level in terms of accuracy, appropriateness, and usefulness, while feasibility was rated at a high level.